Intra-industry trade between Malaysia and Singapore in SITC 7: An ARDL bound test approach - Mui-Yin, Chin; Cia-Ling, Teo; Puah, Chin-Hong (Universiti Putra Malaysia, 2016)
International trade contributes significantly to driving Malaysia's economic growth. As intra-industry trade (IIT) has become increasingly important due to changes in the international trade landscape, this study aims to identify the determinants of IIT and to gauge the trade pattern between Malaysia and Singapore in SITC 7 (the machinery and transport equipment manufacturing sub-sector) from 1980 through 2012 using decompositiontype threshold and Autoregressive Distributed Lag (ARDL) methods. In addition, this study will further decompose IIT into horizontal IIT (HIIT) and vertical IIT (VIIT) to examine the current pattern of IIT. The econometric results reveal that the difference in real gross domestic product (GDP) between the two countries is the key determinant of IIT in both the long run and the short run. Meanwhile, the average of foreign direct investment inflow (FDI) in both countries will stimulate IIT in the short run. Furthermore, the decomposition results confirm that the IIT between the two countries is prone to VIIT. The findings of the empirical results suggest that the policy makers of both countries should leverage the ASEAN Economic Community (AEC) and the Regional Comprehensive Economic Partnership Agreement (RCEP) to enhance their trade ties.